The legacy of Cheryl L. Maxson - Reid, Shannon Elizabeth (The Oxford handbook of gangs and society, 2024)
This chapter highlights the career and impact of Cheryl Maxson on the field of gang research and public criminology. To cover the legacy of Cheryl Maxson, this chapter provides an overview of her non-traditional pathway through academia and her influence on the field and her students. This chapter reviews her large body of work, how she has impacted the field, and how she sees her legacy. To acknowledge Cheryl’s impact on the field is to not only consider her work itself, but her impact as one of the key women working in mainstream criminology, her role as a mentor, and her push for public criminology. Cheryl is rightfully considered one of the pioneering gang scholars, whose work, both nationally and internationally, continues to influence and impact future generations of researchers and policymakers. This chapter also uses the opportunity to interview Cheryl so readers can be inspired by her thoughts about the future of the field and her goals for gang research.